2013
DOI: 10.2140/gt.2013.17.157
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic extension of the earthquake flow I

Abstract: Abstract. Let T be Teichmüller space of a closed surface of genus at least 2. For any point c ∈ T , we describe an action of the circle on T × T , which limits to the earthquake flow when one of the parameters goes to a measured lamination in the Thurston boundary of T . This circle action shares some of the main properties of the earthquake flow, for instance it satisfies an extension of Thurston's Earthquake Theorem and it has a complex extension which is analogous and limits to complex earthquakes. Moreover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(81 citation statements)
references
References 38 publications
0
81
0
Order By: Relevance
“…In [BMS12] it is shown that this landslide flow is Hamiltonian for the product of Weil-Petersson symplectic structures.…”
Section: Complements and Conjecturesmentioning
confidence: 99%
“…In [BMS12] it is shown that this landslide flow is Hamiltonian for the product of Weil-Petersson symplectic structures.…”
Section: Complements and Conjecturesmentioning
confidence: 99%
“…From the proof Proposition 5.5 we have actually shown that, under the assumption Φ(x) = x and that dΦ x = −b, if dσ Φ,b is non-singular at x, then under the identification T id Isom(H 2 ) ∼ = so(2, 1) ∼ = R 2,1 , the future unit normal vector at σ Φ,b (x) = id is N (x) = 2Λ(x). In fact, N (x) = 2Λ(x) is orthogonal to the surface at σ Φ,b (x) by the above observation, and is unit, since the AdS metric at id is identified to 1/4 the Minkowski product, see equation (13).…”
Section: A Representation Formula For Convex Surfacesmentioning
confidence: 91%
“…Let us check the factor in equation (13). By (12) for any x, y ∈ R 2,1 we have ad(Λ(x))(Λ(y)) = Λ(Λ(x)y), that is,…”
Section: Two Useful Modelsmentioning
confidence: 99%
“…Smooth grafting on hyperbolic surfaces with cone singularities. Constant Gauss curvature surfaces in hyperbolic ends are related to the "smooth grafting" map SGr : (0, 1)×T ×T → CP, see [7,Section 1.2]. The properties of K-surfaces in hyperbolic ends with particles as described here show that this "smooth grafting" map is still well-defined on hyperbolic surfaces with cone singularities of angles less than π, as a map SGr θ from (0, 1) × T Σ,θ × T Σ,θ to CP θ .…”
Section: Introductionmentioning
confidence: 99%
“…This implies that for all r ∈ (0, 1), the map SGr θ (r, ·, ·) is a homeomorphism from T Σ,θ × T Σ,θ to CP θ . We do not elaborate on this point here, since it follows from the same arguments as in the non-singular case, see [7]. The relations among all the spaces we consider throughout this paper are presented in Figure 1, which is a combination of Figure 2 1.7.…”
Section: Introductionmentioning
confidence: 99%